Hard‐To‐Sample Species Are More Sensitive to Land‐Use Change: Implications for Global Biodiversity Metrics - Claudia Gutiérrez‐Arellano; Tim Newbold; Jenny A. Hodgson (Global Ecology and Biogeography, 2025)
Aim Land‐use change drives biodiversity loss, but some species are more vulnerable than others. Indicators of global biodiversity must attempt to summarise these impacts representatively and meaningfully, to guide biodiversity recovery. Yet species that are hard to detect, and thus feature less in relevant databases, might possess traits that make them particularly sensitive to anthropogenic impacts. Using global data for plant, bird and spider species, we develop a statistical approach to analyse and correct for the impact of excluding hard‐to‐sample species from global biodiversity indicators. Location Worldwide. Time Period Abundance studies published in 1998–2020; species occurrence records available from 1600 to 2023. Major Taxa Studied Birds, vascular plants and spiders. Methods We first quantified the extent to which the recordability of a species mediates the relationship between site‐level abundance and broad land use type. We used the local abundance data in the Projecting Responses of Ecological Diversity in Changing Terrestrial Systems database (PREDICTS), for over 4000 plant, bird and spider species. As a proxy for species' recordability, we used its number of occurrence records in the Global Biodiversity Information Facility database (GBIF). We then extrapolated our fitted statistical model to all species with valid GBIF occurrence records (0.27 M species). Results Less recordable species tend to decline more as land‐use intensity increases, and problematically, they are underrepresented in PREDICTS. A more representative global indicator can be obtained by extrapolating our model to the hard‐to‐sample, and on average, more sensitive species unobserved in PREDICTS. Our extrapolated, aggregate estimates show a lower abundance of ‘the average species’ in anthropogenic land uses. For example, intensive agriculture only has 18% of the biodiversity level of primary vegetation, rather than the 47% estimated without extrapolation to the hard‐to‐sample species. Main Conclusions Given the bias encountered in PREDICTS and the considerable difference in abundance change estimations, we recommend that other existing indicators include an extrapolation solution based on ours to incorporate the available data as effectively as possible. Using occurrence data to predict species' sensitivity unlocks many possibilities to improve global biodiversity indicators by enhancing their overall coverage and accuracy, without demanding additional data on poorly known species.

Bumble Bee Probability of Occurrence Responds to Interactions Between Local and Landscape Land Use, Climatic Niche Properties and Climate Change - Tim Newbold; Jeremy Kerr; Peter Soroye; Jessica J. Williams (Ecology Letters, 2025)
Insect biodiversity is changing rapidly, driven by a suite of pressures, notably land use, land‐use intensification and increasingly climate change. We lack large‐scale evidence on how land use and climate change interact to drive insect biodiversity changes. We assess bumble bee responses to interactive effects of land use and climate pressures across North America and Europe. The probability of occurrence increases in landscapes with a higher proportion of natural habitat and a shorter history of human disturbance. Responses to climate warming relative to historical conditions are weakly negative in natural habitats but positive in human land uses, while human land use reduces the probability of occurrence most in the centre of species' temperature niches. We estimate that the combined pressures have reduced bumble bee probability of occurrence by 44% across sampled natural habitats and 55% across human land uses, highlighting the pervasive influence that human pressures have had on biodiversity across habitats.

Trends in habitat quality and habitat degradation in terrestrial protected areas - Jianqiao Zhao; Le Yu; Tim Newbold; Xin Chen (Conservation Biology, 2025)
Protected areas are typically considered a cornerstone of conservation programs and play a fundamental role in protecting natural areas and biodiversity. Human‐driven land‐use and land‐cover (LULC) changes lead to habitat loss and biodiversity loss inside protected areas, impairing their effectiveness. However, the global dynamics of habitat quality and habitat degradation in protected areas remain unclear. We used the Integrated Valuation of Ecosystem Services and Trade‐offs (InVEST) model based on global annual remotely sensed data to examine the spatial and temporal trends in habitat quality and degradation in global terrestrial protected areas. Habitat quality represented the ability of habitats to provide suitable conditions for the persistence of individuals and populations, and habitat degradation represented the impacts on habitats from human‐driven LULC changes in the surrounding landscape. Based on a linear mixed‐effects modeling method, we also explored the relationship between habitat degradation trends and protected area characteristics, biophysical factors, and socioeconomic factors. Habitat quality declined by 0.005 (0.6%) and habitat degradation increased by 0.002 (11%) from 1992 to 2020 globally, and similar trends occurred even in remote or restrictively managed protected areas. Habitat degradation was attributed primarily to nonirrigated cropland (62%) and urbanization (27%) in 2020. Increases in elevation, gross domestic production per capita, and human population density and decreases in agricultural suitability were associated with accelerated habitat degradation. Our results suggest that human‐induced LULC changes have expanded from already‐exploited areas into relatively undisturbed areas, and that in wealthy countries in particular, degradation is related to rapid urbanization and increasing demand for agricultural products.

Impact of Crop Type on Biodiversity Globally - Shunxiang Fan; Tim Newbold; Teja Tscharntke; Wenhui Tang; Zhenrong Yu; Yunhui Liu (Global Change Biology, 2024)
The negative impact of agricultural land on biodiversity is widely recognized. However, there remains a knowledge gap regarding the role of different crop types in maintaining biodiversity within the agricultural landscape. By extracting biodiversity data from global datasets and classifying different crop types, we quantified the contribution of different crop types to biodiversity. Our results indicate that biodiversity levels vary widely among crop types. We found a general loss of biodiversity when natural vegetation is converted to agricultural land, and highest losses in fiber crops, cereals and oil crops, and least in other crops (such as coffee or cocoa) and in mixed crops. In general, perennial crops retain more biodiversity than annual crops. Losses of biodiversity can be mitigated through mixed cropping of multiple crop types, especially by combining annual and perennial crops. The negative impact of converting natural vegetation to agriculture is greater in tropical than in nontropical areas, and hence, the import of commodities from these biodiversity‐rich regions may be particularly detrimental. Given the ongoing increase in biodiversity losses from global intensification and expansion of agricultural land, maintaining or restoring natural vegetation, rating the crop‐type‐specific biodiversity, diversifying crops, and preferring perennial over annual crops, particularly in the tropics, need to be better considered and implemented in global agri‐environmental schemes.

Species‐level correlates of land‐use responses and climate‐change sensitivity in terrestrial vertebrates - Adrienne Etard; Tim Newbold (Conservation Biology, 2024)
Land‐use and climate change are major pressures on terrestrial biodiversity. Species’ extinction risk and responses to human pressures relate to ecological traits and other characteristics in some clades. However, large‐scale comparative assessments of the associations between traits and responses to multiple human pressures across multiple clades are needed. We investigated whether a set of ecological characteristics that are commonly measured across terrestrial vertebrates (ecological traits and geographic range area) are associated with species’ responses to different land‐use types and species’ likely sensitivity to climate change. We aimed to test whether generalizable patterns in response to these pressures arise across both pressures and across vertebrate clades, which could inform assessments of the global signature of human pressures on vertebrate biodiversity and guide conservation efforts. At the species level, we investigated associations between land‐use responses and ecological characteristics with a space‐for‐time substitution approach, making use of the PREDICTS database. We investigated associations between ecological characteristics and expected climate‐change sensitivity, estimated from properties of species realized climatic niches. Among the characteristics we considered, 3 were consistently associated with strong land‐use responses and high climate‐change sensitivity across terrestrial vertebrate classes: narrow geographic range, narrow habitat breadth, and specialization on natural habitats (which described whether a species occurs in artificial habitats or not). The associations of other traits with species’ land‐use responses and climate‐change sensitivity often depended on species’ class and land‐use type, highlighting an important degree of context dependency. In all classes, invertebrate eaters and fruit and nectar eaters tended to be negatively affected in disturbed land‐use types, whereas invertebrate‐eating and plant‐ and seed‐eating birds were estimated to be more sensitive to climate change, raising concerns about the continuation of ecological processes sustained by these species under global changes. Our results highlight a consistently higher sensitivity of narrowly distributed species and habitat specialists to land‐use and climate change, which provides support for capturing such characteristics in large‐scale vulnerability assessments.

Biodiversity responses to agricultural practices in cropland and natural habitats - Jianqiao Zhao; Le Yu; Tim Newbold; Xiaoli Shen; Xiaoxuan Liu; Fangyuan Hua; Kasturi Kanniah; Keping Ma (Science of The Total Environment, 2024)

Climate change disrupts the seasonal coupling of plant and soil microbial nutrient cycling in an alpine ecosystem - Arthur A. D. Broadbent; Lindsay K. Newbold; William J. Pritchard; Antonios Michas; Tim Goodall; Irene Cordero; Andrew Giunta; Helen S. K. Snell; Violette V. L. H. Pepper; Helen K. Grant; David X. Soto; Ruediger Kaufmann; et al. (Global Change Biology, 2024)
The seasonal coupling of plant and soil microbial nutrient demands is crucial for efficient ecosystem nutrient cycling and plant production, especially in strongly seasonal alpine ecosystems. Yet, how these seasonal nutrient cycling processes are modified by climate change and what the consequences are for nutrient loss and retention in alpine ecosystems remain unclear. Here, we explored how two pervasive climate change factors, reduced snow cover and shrub expansion, interactively modify the seasonal coupling of plant and soil microbial nitrogen (N) cycling in alpine grasslands, which are warming at double the rate of the global average. We found that the combination of reduced snow cover and shrub expansion disrupted the seasonal coupling of plant and soil N‐cycling, with pronounced effects in spring (shortly after snow melt) and autumn (at the onset of plant senescence). In combination, both climate change factors decreased plant organic N‐uptake by 70% and 82%, soil microbial biomass N by 19% and 38% and increased soil denitrifier abundances by 253% and 136% in spring and autumn, respectively. Shrub expansion also individually modified the seasonality of soil microbial community composition and stoichiometry towards more N‐limited conditions and slower nutrient cycling in spring and autumn. In winter, snow removal markedly reduced the fungal:bacterial biomass ratio, soil N pools and shifted bacterial community composition. Taken together, our findings suggest that interactions between climate change factors can disrupt the temporal coupling of plant and soil microbial N‐cycling processes in alpine grasslands. This could diminish the capacity of these globally widespread alpine ecosystems to retain N and support plant productivity under future climate change.

Assessing the global vulnerability of dryland birds to heatwaves - Chenchen Ding; Tim Newbold; Eric I. Ameca (Global Change Biology, 2024)
As global average surface temperature increases, extreme climatic events such as heatwaves are becoming more frequent and intense, which can drive biodiversity responses such as rapid population declines and/or shifts in species distributions and even local extirpations. However, the impacts of extreme climatic events are largely ignored in conservation plans. Birds are known to be susceptible to heatwaves, especially in dryland ecosystems. Understanding which birds are most vulnerable to heatwaves, and where these birds occur, can offer a scientific basis for adaptive management and conservation. We assessed the relative vulnerability of 1196 dryland bird species to heatwaves using a trait‐based approach. Among them, 888 bird species are estimated to be vulnerable to heatwaves (170 highly vulnerable, eight extremely vulnerable), of which ~91% are currently considered non‐threatened by the IUCN, which suggests that many species will likely become newly threatened with intensifying climate change. We identified the top three hotspot areas of heatwave‐vulnerable species in Australia (208 species), Southern Africa (125 species) and Eastern Africa (99 species). Populations of vulnerable species recorded in the Living Planet Database were found to be declining significantly faster than those of non‐vulnerable species ( p = .048) after heatwaves occurred. In contrast, no significant difference in population trends between vulnerable and non‐vulnerable species was detected when no heatwave occurred ( p = .34). This suggests that our vulnerability framework correctly identified vulnerable species and that heatwaves are already impacting the population trends of these species. Our findings will help prioritize heatwave‐vulnerable birds in dryland ecosystems in risk mitigation and adaptation management as the frequency of heatwaves accelerates in the coming decades.

Species life‐history strategies affect population responses to temperature and land‐cover changes - Gonzalo Albaladejo‐Robles; Monika Böhm; Tim Newbold (Global Change Biology, 2023)
Human‐induced environmental changes have a direct impact on species populations, with some species experiencing declines while others display population growth. Understanding why and how species populations respond differently to environmental changes is fundamental to mitigate and predict future biodiversity changes. Theoretically, species life‐history strategies are key determinants shaping the response of populations to environmental impacts. Despite this, the association between species life histories and the response of populations to environmental changes has not been tested. In this study, we analysed the effects of recent land‐cover and temperature changes on rates of population change of 1,072 populations recorded in the Living Planet Database. We selected populations with at least 5 yearly consecutive records (after imputation of missing population estimates) between 1992 and 2016, and for which we achieved high population imputation accuracy (in the cases where missing values had to be imputed). These populations were distributed across 553 different locations and included 461 terrestrial amniote vertebrate species (273 birds, 137 mammals, and 51 reptiles) with different life‐history strategies. We showed that populations of fast‐lived species inhabiting areas that have experienced recent expansion of cropland or bare soil present positive populations trends on average, whereas slow‐lived species display negative population trends. Although these findings support previous hypotheses that fast‐lived species are better adapted to recover their populations after an environmental perturbation, the sensitivity analysis revealed that model outcomes are strongly influenced by the addition or exclusion of populations with extreme rates of change. Therefore, the results should be interpreted with caution. With climate and land‐use changes likely to increase in the future, establishing clear links between species characteristics and responses to these threats is fundamental for designing and conducting conservation actions. The results of this study can aid in evaluating population sensitivity, assessing the likely conservation status of species with poor data coverage, and predicting future scenarios of biodiversity change.

Development of climate tipping damage metric for life-cycle assessment—the influence of increased warming from the tipping - Serena Fabbri; Mikołaj Owsianiak; Tim Newbold; Michael Z. Hauschild (The International Journal of Life Cycle Assessment, 2022)

Prioritizing conservation in sub‐Saharan African lakes based on freshwater biodiversity and algal bloom metrics - Cody Danaher; Tim Newbold; Jeffrey Cardille; Abbie S. A. Chapman (Conservation Biology, 2022)
As agricultural land use and climate change continue to pose increasing threats to biodiversity in sub‐Saharan Africa, efforts are being made to identify areas where trade‐offs between future agricultural development and terrestrial biodiversity conservation are expected to be greatest. However, little research so far has focused on freshwater biodiversity conservation in the context of agricultural development in sub‐Saharan Africa. We aimed to identify lakes and lake areas where freshwater biodiversity is most likely to be affected by eutrophication and Harmful Algal Blooms (i.e., when algae multiply to the extent that they have toxic effects on people and freshwater fauna), some of the most important emerging threats to freshwater ecosystems worldwide, especially with the onset of climate change. Using novel remote‐sensing techniques, we identified lakes that demonstrated high biodiversity and algal bloom levels. We calculated the richness of freshwater species and the normalized difference chlorophyll index (NDCI) to prioritize lakes in Ghana, Ethiopia, Zambia, and bordering countries, of high priority for conservation. We identified 169 priority lakes and lake areas for conservation, based on high levels of biodiversity exposed to potentially harmful algal blooms. Zambia had the most lakes identified as conservation priorities (76% of its small lakes and five 100‐km 2 areas in large lakes). Many of the conservation priority lakes and lake areas identified in this study were in transboundary watersheds; thus, collaborative water resource management and conservation at the watershed scale is needed. The use of remote‐sensing tools to prioritize freshwater systems for conservation according to algal‐bloom risk is vital in remote, undersampled world regions, especially given the increasing threat posed to freshwater biodiversity by rapidly expanding agriculture and climate change.

Availability and proximity of natural habitat influence cropland biodiversity in forest biomes globally - Charlotte L. Outhwaite; A. Monica D. Ortiz; Fiona E. B. Spooner; Carole Dalin; Tim Newbold (Global Ecology and Biogeography, 2022)
Aim Agriculture is one of the greatest pressures on biodiversity. Regional studies have shown that the presence of natural habitat and landscape heterogeneity are beneficial for biodiversity in agriculture, but it remains unclear whether their importance varies geographically. Here, we use local biodiversity data to determine which local and landscape variables are most associated with biodiversity patterns and whether their association varies between tropical and non‐tropical regions. Location Global terrestrial area in forest biomes. Major taxa studied More than 21,000 species of vertebrates, invertebrates, plants and other taxa. Methods We used generalized linear mixed‐effects models to analyse the relationships between either community total abundance or species richness (derived from the PREDICTS database) and a number of site‐level (predominant land use and land‐use intensity) and landscape‐level variables (distance to forest, the percentage of natural habitat in the surrounding landscape, landscape homogeneity, the number of land‐cover types in the landscape, and total fertilizer application). We compared the associations of these variables with biodiversity in tropical and non‐tropical regions. Results In most cases, changes in biodiversity associated with landscape‐level variables were greater than those associated with local land use and land‐use intensity. Increased natural habitat availability was associated with the most consistent increases in biodiversity. Landscape homogeneity was also important but showed different directions of biodiversity change between regions. Associations with fertilizer application or the number of land‐cover types were generally weaker, although still of greater magnitude than for the local land‐use measures. Main conclusions Our results highlight similarities and differences in the association of local‐ and landscape‐scale variables with local biodiversity in tropical and non‐tropical regions. Landscape natural habitat availability had a consistent positive association with biodiversity, highlighting the key role of landscape management in the maintenance of biodiversity in croplands. Landscape‐scale variables were almost always associated with greater changes in biodiversity than the local‐scale measures.

Vertebrate population trends are influenced by interactions between land use, climatic position, habitat loss and climate change - Jessica J. Williams; Robin Freeman; Fiona Spooner; Tim Newbold (Global Change Biology, 2022)
Rapid human‐driven environmental changes are impacting animal populations around the world. Currently, land‐use and climate change are two of the biggest pressures facing biodiversity. However, studies investigating the impacts of these pressures on population trends often do not consider potential interactions between climate and land‐use change. Further, a population's climatic position (how close the ambient temperature and precipitation conditions are to the species’ climatic tolerance limits) is known to influence responses to climate change but has yet to be investigated with regard to its influence on land‐use change responses over time. Consequently, important variations across species’ ranges in responses to environmental changes may be being overlooked. Here, we combine data from the Living Planet and BioTIME databases to carry out a global analysis exploring the impacts of land use, habitat loss, climatic position, climate change and the interactions between these variables, on vertebrate population trends. By bringing these datasets together, we analyse over 7,000 populations across 42 countries. We find that land‐use change is interacting with climate change and a population's climatic position to influence rates of population change. Moreover, features of a population's local landscape (such as surrounding land cover) play important roles in these interactions. For example, populations in agricultural land uses where maximum temperatures were closer to their hot thermal limit, declined at faster rates when there had also been rapid losses in surrounding semi‐natural habitat. The complex interactions between these variables on populations highlight the importance of taking intraspecific variation and interactions between local and global pressures into account. Understanding how drivers of change are interacting and impacting populations, and how this varies spatially, is critical if we are to identify populations at risk, predict species’ responses to future environmental changes and produce suitable conservation strategies.

Intensive human land uses negatively affect vertebrate functional diversity - Adrienne Etard; Alex L. Pigot; Tim Newbold (Ecology Letters, 2022)
Land‐use change is the leading driver of global biodiversity loss thus characterising its impacts on the functional structure of ecological communities is an urgent challenge. Using a database describing vertebrate assemblages in different land uses, we assess how the type and intensity of land use affect the functional diversity of vertebrates globally. We find that human land uses alter local functional structure by driving declines in functional diversity, with the strongest effects in the most disturbed land uses (intensely used urban sites, cropland and pastures), and among amphibians and birds. Both tropical and temperate areas experience important functional losses, which are only partially offset by functional gains. Tropical assemblages are more likely to show decreases in functional diversity that exceed those expected from species loss alone. Our results indicate that land‐use change non‐randomly reshapes the functional structure of vertebrate assemblages, raising concerns about the continuation of ecological processes sustained by vertebrates.

Shrub expansion modulates belowground impacts of changing snow conditions in alpine grasslands - Arthur A. D. Broadbent; Michael Bahn; William J. Pritchard; Lindsay K. Newbold; Tim Goodall; Andrew Guinta; Helen S. K. Snell; Irene Cordero; Antonios Michas; Helen K. Grant; David X. Soto; Rüdiger Kaufmann; et al. (Ecology Letters, 2022)
Climate change is disproportionately impacting mountain ecosystems, leading to large reductions in winter snow cover, earlier spring snowmelt and widespread shrub expansion into alpine grasslands. Yet, the combined effects of shrub expansion and changing snow conditions on abiotic and biotic soil properties remains poorly understood. We used complementary field experiments to show that reduced snow cover and earlier snowmelt have effects on soil microbial communities and functioning that persist into summer. However, ericaceous shrub expansion modulates a number of these impacts and has stronger belowground effects than changing snow conditions. Ericaceous shrub expansion did not alter snow depth or snowmelt timing but did increase the abundance of ericoid mycorrhizal fungi and oligotrophic bacteria, which was linked to decreased soil respiration and nitrogen availability. Our findings suggest that changing winter snow conditions have cross‐seasonal impacts on soil properties, but shifts in vegetation can modulate belowground effects of future alpine climate change.

A research perspective towards a more complete biodiversity footprint: a report from the World Biodiversity Forum - Alexandra Marques; Marine Robuchon; Stefanie Hellweg; Tim Newbold; Jutta Beher; Sebastian Bekker; Franz Essl; Daniele Ehrlich; Samantha Hill; Martin Jung; Sandra Marquardt; Francesca Rosa; et al. (The International Journal of Life Cycle Assessment, 2021)

Global gaps in trait data for terrestrial vertebrates - Adrienne Etard; Sophie Morrill; Tim Newbold (Global Ecology and Biogeography, 2020)
Aim Trait data are increasingly being used in studies investigating the impacts of global changes on the structure and functioning of ecological communities. Despite a growing number of trait data collations for terrestrial vertebrates, there is to date no global assessment of the gaps and biases the data present. Here, we assess whether terrestrial vertebrate trait data are taxonomically, spatially and phylogenetically biased. Location Global. Time period Present. Major taxa studied Terrestrial vertebrates. Methods We compile seven ecological traits and quantify coverage as the proportion of species for which an estimate is available. For a species, we define completeness as the proportion of non‐missing values across traits. We assess whether coverage and completeness differ across classes and examine phylogenetic biases in trait data. To investigate spatial biases, we test whether wider‐ranging species have more complete trait data than narrow‐ranging species. Additionally, we test whether species‐rich regions, which are of most concern for conservation, are less well sampled than species‐poor regions. Results Mammals and birds are well sampled even in species‐rich regions. For reptiles and amphibians (herptiles), only body size presents a high coverage (>80%), in addition to habitat‐related variables (amphibians). Herptiles are poorly sampled for other traits. The shortfalls are particularly acute in some species‐rich regions and for certain clades. Across all classes, geographically rarer species have less complete trait information. Main conclusions Trait information is less available on average in some of the most diverse areas and in geographically rarer species, both of which crucial for biodiversity conservation. Gaps in trait data might impede our ability to conduct large‐scale analyses, whereas biases can impact the validity of extrapolations. A short‐term solution to the problem is to estimate missing trait data using imputation techniques, whereas a longer‐term and more robust filling of existing gaps requires continued data‐collection efforts.

Effects of rarity form on species’ responses to land use - Louise Sykes; Luca Santini; Adrienne Etard; Tim Newbold (Conservation Biology, 2020)
Anthropogenic land‐use change causes substantial changes in local and global biodiversity. Rare and common species can differ in sensitivity to land‐use change; rare species are expected to be affected more negatively. Rarity may be defined in terms of geographic range size, population density, or breadth of habitat requirements. How these 3 forms of rarity interact in determining global responses to land use is yet to be assessed. Using global data representing 912 vertebrate species, we tested for differences in responses to land use of species characterized by different types of rarity. Land‐use responses were fitted using generalized linear mixed‐effects models, allowing responses to vary among groups of species with different forms of rarity. Species considered rare with respect to all 3 forms of rarity showed particularly strong declines in disturbed land uses (>40% of species and 30% of individuals in the most disturbed land uses). In contrast, species common both geographically and numerically and with broad habitat requirements showed strong increases (up to 90% increase in species and 40% in abundance in some land uses). Our results suggest that efforts to understand the vulnerability of species to environmental changes should account for different types of rarity where possible. Our results also have potentially important implications for ecosystem functioning, given that rare species may play unique roles within ecosystems.

Assessing the effects of land use on biodiversity in the world’s drylands and Mediterranean environments - Diego García-Vega; Tim Newbold (Biodiversity and Conservation, 2020)
Biodiversity models make an important contribution to our understanding of global biodiversity changes. The effects of different land uses vary across ecosystem types, yet most broad-scale models have failed to account for this variation. The effects of land use may be different in systems characterized by low water availability because of the unusual conditions within these systems. Drylands are expanding, currently occupying over 40% of the terrestrial land, while Mediterranean systems are highly endangered biodiversity hotspots. However, the impact of land use on biodiversity in these biomes is yet to be assessed. Using a database of local biodiversity surveys, we assess the effects of land use on biodiversity in the world’s drylands and Mediterranean ecosystems. We compare the average species richness, total abundance, species diversity, ecological dominance, endemism rates, and compositional turnover across different land uses. In drylands, there was a strong turnover in species composition in disturbed land uses compared with undisturbed natural habitat (primary vegetation), but other measures of biodiversity did not respond significantly. However, it is important to note that the sample size for drylands was very low, a gap which should be filled promptly. Mediterranean environments showed a very high sensitivity of biodiversity to land uses. In this biome, even habitat recovering after past disturbance (secondary vegetation) had substantially reduced biodiversity and altered community composition compared with primary vegetation. In an effort to maintain original biodiversity and the ecosystem functions it supports within Mediterranean biomes, conservation measures should therefore prioritize the preservation of remaining primary vegetation.

Conventional land‐use intensification reduces species richness and increases production: A global meta‐analysis - Michael Beckmann; Katharina Gerstner; Morodoluwa Akin‐Fajiye; Silvia Ceaușu; Stephan Kambach; Nicole L. Kinlock; Helen R. P. Phillips; Willem Verhagen; Jessica Gurevitch; Stefan Klotz; Tim Newbold; Peter H. Verburg; et al. (Global Change Biology, 2019)
Most current research on land‐use intensification addresses its potential to either threaten biodiversity or to boost agricultural production. However, little is known about the simultaneous effects of intensification on biodiversity and yield. To determine the responses of species richness and yield to conventional intensification, we conducted a global meta‐analysis synthesizing 115 studies which collected data for both variables at the same locations. We extracted 449 cases that cover a variety of areas used for agricultural (crops, fodder) and silvicultural (wood) production. We found that, across all production systems and species groups, conventional intensification is successful in increasing yield (grand mean + 20.3%), but it also results in a loss of species richness (−8.9%). However, analysis of sub‐groups revealed inconsistent results. For example, small intensification steps within low intensity systems did not affect yield or species richness. Within high‐intensity systems species losses were non‐significant but yield gains were substantial (+15.2%). Conventional intensification within medium intensity systems revealed the highest yield increase (+84.9%) and showed the largest loss in species richness (−22.9%). Production systems differed in their magnitude of richness response, with insignificant changes in silvicultural systems and substantial losses in crop systems (−21.2%). In addition, this meta‐analysis identifies a lack of studies that collect robust biodiversity (i.e. beyond species richness) and yield data at the same sites and that provide quantitative information on land‐use intensity. Our findings suggest that, in many cases, conventional land‐use intensification drives a trade‐off between species richness and production. However, species richness losses were often not significantly different from zero, suggesting even conventional intensification can result in yield increases without coming at the expense of biodiversity loss. These results should guide future research to close existing research gaps and to understand the circumstances required to achieve such win‐win or win‐no‐harm situations in conventional agriculture.

Land-use effects on local biodiversity in tropical forests vary between continents - Helen R. P. Phillips; Tim Newbold; Andy Purvis (Biodiversity and Conservation, 2017)

Functional traits, land‐use change and the structure of present and future bird communities in tropical forests - Tim Newbold; Jörn P. W. Scharlemann; Stuart H. M. Butchart; Çağan H. Şekercioğlu; Lucas Joppa; Rob Alkemade; Drew W. Purves (Global Ecology and Biogeography, 2014)
Aim Habitat loss continues to cause loss of biodiversity. To quantify the effects of land‐use change on the diversity and composition of ecological communities – in terms of functional groups – we make modelled estimates of the impact of past and future (to 2050) land‐use change on the overall diversity and dietary guild structure of tropical forest bird communities. Location Tropical and subtropical forests (40° S to 40° N ). Methods Using a likelihood‐based model, we project the impact of land‐use intensity on the diversity and functional structure of tropical forest bird communities, including an estimation of uncertainty. To explore the extent to which predicted impacts are determined by the inherent sensitivity of communities because of the traits possessed by the species present, we quantify communities in terms of trait composition and explore relationships between trait composition and diversity/guild loss. Results We estimate that habitat loss has led to an average decrease of 4% in total abundance, but with marked differences across different guilds, leading to substantial changes in community composition: an 11.4% loss of frugivores, 7.8% loss of nectarivores and 7.3% loss of insectivores, and a 4.0% gain of other herbivores. Projected land‐use change is predicted to result in average future losses of 1% of total abundance, 1% of each of frugivores, nectarivores and insectivores, but no average change in the abundance of other herbivores. Past and future changes have varied substantially across the biome, owing to variation in land‐use change and in the initial trait composition of communities. Main conclusions We predict that marked changes in community structure have occurred in the past and will occur in the future, with disproportionate losses of frugivores, nectarivores and insectivores compared with other species; these species are known to provide important ecosystem services. In the past, South America has been particularly strongly affected, while Southeast Asia will experience the strongest impacts in the future.

Integrated assessment models for ecologists: the present and the future - Michael Harfoot; Derek P. Tittensor; Tim Newbold; Greg McInerny; Matthew J. Smith; Jörn P. W. Scharlemann (Global Ecology and Biogeography, 2014)
Aim Human impacts on the biosphere are a matter of urgent and growing concern, with ecologists increasingly being asked to project biodiversity futures. The Intergovernmental Platform on Biodiversity and Ecosystem Services ( IPBES ) is likely to comprehensively assess such projections, yet despite being widely used and potentially critical tools for analysing socio‐environmental futures, integrated assessment models ( IAM s) have received little attention from ecological modellers. We aim to raise awareness and understanding of IAM s among ecologists by describing the structure and composition of IAM s, assessing their utility for biodiversity projections and identifying limitations that hamper greater interaction between scientists using IAMs and those using ecological models. We also hope to inspire more accessible and applicable models by suggesting development needs for IAM s. Methods We conduct a systematic review of four state‐of‐the‐art IAM s, which describes and contrasts key model features and analyses six aspects of IAM s that are of fundamental interest to ecologists. Conclusions IAM s could be valuable for modelling biodiversity futures; however, current IAM s were not developed for this application and challenges remain for ecologists looking to use their outputs. Separating and understanding the differences resulting from IAM formulation and those resulting from specific scenario assumptions is currently problematic, and current IAM s may be unable to accurately represent environmental conditions for both Earth‐system projections and for building robust models of biodiversity because key ecological processes are absent. We suggest that model intercomparisons would identify differences in model dynamics, and detailed studies of how dynamical interactions between components influence behaviour would address why such differences arise. Bio‐economic fisheries models and agriculture pollination models provide starting points for integrating key ecological feedbacks within IAM s. Ultimately, making IAM s more accessible within the multidisciplinary study of global change, drawing on user‐centred research, would enable more resolved, reliable and accurate assessment of how Earth's socio‐ecological system is approaching planetary boundaries.

The response of marine picoplankton to ocean acidification - Lindsay K. Newbold; Anna E. Oliver; Tim Booth; Bela Tiwari; Todd DeSantis; Michael Maguire; Gary Andersen; Christopher J. van der Gast; Andrew S. Whiteley (Environmental Microbiology, 2012)
Summary Since industrialization global CO 2 emissions have increased, and as a consequence oceanic pH is predicted to drop by 0.3–0.4 units before the end of the century – a process coined ‘ocean acidification’. Consequently, there is significant interest in how pH changes will affect the ocean's biota and integral processes. We investigated marine picoplankton (0.2–2 µm diameter) community response to predicted end of century CO 2 concentrations, via a ‘high‐CO 2 ’ (∼ 750 ppm) large‐volume (11 000 l) contained seawater mesocosm approach. We found little evidence of changes occurring in bacterial abundance or community composition due to elevated CO 2 under both phytoplankton pre‐bloom/bloom and post‐bloom conditions. In contrast, significant differences were observed between treatments for a number of key picoeukaryote community members. These data suggested a key outcome of ocean acidification is a more rapid exploitation of elevated CO 2 levels by photosynthetic picoeukaryotes. Thus, our study indicates the need for a more thorough understanding of picoeukaryote‐mediated carbon flow within ocean acidification experiments, both in relation to picoplankton carbon sources, sinks and transfer to higher trophic levels.

Effect of characteristics of butterfly species on the accuracy of distribution models in an arid environment - Tim Newbold; Tom Reader; Samy Zalat; Ahmed El-Gabbas; Francis Gilbert (Biodiversity and Conservation, 2009)

The seasonal structure of microbial communities in the Western English Channel - Jack A. Gilbert; Dawn Field; Paul Swift; Lindsay Newbold; Anna Oliver; Tim Smyth; Paul J. Somerfield; Sue Huse; Ian Joint (Environmental Microbiology, 2009)
Summary Very few marine microbial communities are well characterized even with the weight of research effort presently devoted to it. Only a small proportion of this effort has been aimed at investigating temporal community structure. Here we present the first report of the application of high‐throughput pyrosequencing to investigate intra‐annual bacterial community structure. Microbial diversity was determined for 12 time points at the surface of the L4 sampling site in the Western English Channel. This was performed over 11 months during 2007. A total of 182 560 sequences from the V6 hyper‐variable region of the small‐subunit ribosomal RNA gene (16S rRNA) were obtained; there were between 11 327 and 17 339 reads per sample. Approximately 7000 genera were identified, with one in every 25 reads being attributed to a new genus; yet this level of sampling far from exhausted the total diversity present at any one time point. The total data set contained 17 673 unique sequences. Only 93 (0.5%) were found at all time points, yet these few lineages comprised 50% of the total reads sequenced. The most abundant phylum was Proteobacteria ( 50% of all sequenced reads), while the SAR11 clade comprised 21% of the ubiquitous reads and ∼12% of the total sequenced reads. In contrast, 78% of all operational taxonomic units were only found at one time point and 67% were only found once, evidence of a large and transient rare assemblage. This time series shows evidence of seasonally structured community diversity. There is also evidence for seasonal succession, primarily reflecting changes among dominant taxa. These changes in structure were significantly correlated to a combination of temperature, phosphate and silicate concentrations.

Climate‐based models of spatial patterns of species richness in Egypt’s butterfly and mammal fauna - Tim Newbold; Francis Gilbert; Samy Zalat; Ahmed El‐Gabbas; Tom Reader (Journal of Biogeography, 2009)
Aim Identifying areas of high species richness is an important goal of conservation biogeography. In this study we compared alternative methods for generating climate‐based estimates of spatial patterns of butterfly and mammal species richness. Location Egypt. Methods Data on the occurrence of butterflies and mammals in Egypt were taken from an electronic database compiled from museum records and the literature. Using M axent , species distribution models were built with these data and with variables describing climate and habitat. Species richness predictions were made by summing distribution models for individual species and by modelling observed species richness directly using the same environmental variables. Results Estimates of species richness from both methods correlated positively with each other and with observed species richness. Protected areas had higher species richness (both predicted and actual) than unprotected areas. Main conclusions Our results suggest that climate‐based models of species richness could provide a rapid method for selecting potential areas for protection and thus have important implications for biodiversity conservation.